2018
DOI: 10.1055/a-0759-0140
|View full text |Cite
|
Sign up to set email alerts
|

Druckverhältnisse bei Verwendung miniaturisierter PNL-Schäfte mit 9,5 Ch bzw. 12 Ch Außendurchmesser für die minimalinvasive perkutane Nephrolitholapaxie (MIP): Ex-vivo-Druckstudien

Abstract: Zusammenfassung Hintergrund In den letzten Jahren wurde die Entwicklung miniaturisierter Amplatz-Schäfte für die perkutane Nephrolitholapaxie mit dem Ziel eines verringerten Nierentraumas vorangetrieben. Bisherige Studien konnten zwar vergleichbar gute Steinfreiheitsraten im Vergleich zur herkömmlichen PNL bestätigen, jedoch zeigten sich ebenfalls vergleichbare Häufigkeiten postoperativen Fiebers bzw. Septikämien. Als mögliche Ursache hierfür wird der Einfluss der intraoperativen intrapelvinen Drücke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Huusman et al reported a study of intrarenal pressure with 9.5 Fr and 12 Fr nephroscopes in an ex vivo organ model. In a PCNL experiment using an ultra-thin nephroscope, when a mono-J-catheter was placed in the renal pelvis and suction was applied, the intrapelvic pressure did not exceed 30 mmHg at a normal perfusion pressure [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Huusman et al reported a study of intrarenal pressure with 9.5 Fr and 12 Fr nephroscopes in an ex vivo organ model. In a PCNL experiment using an ultra-thin nephroscope, when a mono-J-catheter was placed in the renal pelvis and suction was applied, the intrapelvic pressure did not exceed 30 mmHg at a normal perfusion pressure [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not examine renal pelvic pressure with or without an instrument inserted in the working channel of the nephroscope or f-URS. Doizi et al reported that inserting a 173 μm laser through the working channel of the nephroscope reduced intrarenal pelvic pressure by up to 9.7 cmH 2 O (7.1 mmHg) [ 18 ]. However, in this study, the maximum renal pelvic pressure was 109.5 mmHg when an ultra-thin nephroscope was used, and there is a high possibility of dangerous renal pelvic pressure, regardless of the use of the working channel.…”
Section: Discussionmentioning
confidence: 99%